Determination of Essential Elements in Indian Rice Samples Before and After Washing by ICP-MS - M. Al-Mohaimeed, Amal; Al-Harbi, H.F.A. (Asian Journal of Chemistry, 2020)
In this study, a simple analytical technique was established to determine the content of essential elements (K, P, Mg, Ca, Zn, and Cu) in four samples of Indian rice. The influence of soaking, washing, and cooking on the essential elements concentration was determined. Twenty samples employed in this study, were contained in closed vessels and subjected to microwave-assisted digestion. Six elements (K, P, Ca, Mg, Zn, and Cu) were analyzed and determined through inductively coupled plasma mass spectrometry (ICP-MS). In the analyzed elements, the concentration of potassium elements and phosphate was the highest and that of zinc and copper was the lowest. The low values of the limits of detection (LOD) and limits of quantification (LOQ) with a relative standard deviation (%RSD) of 0.2-3% were observed.